نظام المشيخة ودوره في إدارة شؤون المهاجرين الجزائريين في تونس 1881 – 1956 م - دريد حمو (University Eloued جامعة الوادي, 2024)
الملخص: شهدت تونس مع الاحتلال الفرنسي للجزائر سنة 1830م، تزايد لعدد المهاجرين الجزائريين الذين لجأوا إليها هروبا من الممارسات القمعية الفرنسية تجاه الشعب الجزائري وحفاظا على هويتهم الوطنية، وبما أن تونس كانت الوجهة الأولى للمهاجرين الجزائريين، الذين استقروا هناك في مناطق متعددة، وكان لهم حضور سياسي واقتصادي، واجتماعي وثقافي ومن هنا فقد عمدت الحكومة التونسية، ثم سلطة الحماية الفرنسية على إيجاد تنظيم إداري يتولى إدارة شؤون المهاجريين الجزائريين بتونس من خلال تفعيل نظام المشيخة، هذا النظام الذي سيكون حلقة الوصل بين المهاجرين الجزائريين المتواجدين في تونس، وسلطة الإقامة الفرنسية والحكومة التونسية، بما يخدم عموما ارادة الحماية الفرنسية في تونس ما بين 1881 1956م عرف تنظيم المشيخة الجزائرية في تونس خلال فترة الحماية الفرنسية 1881-1956م عدة تطورات، تحول فيها الى نظام عرفي يدير مجتمع المهاجرين الجزائريين في مدينة تونس ويمثلهم لدى الحكومة التونسية، الى تنظيم يشمل جميع المهاجريين الجزائريين في البلاد التونسية، ووضعت مجموعة من الشروط للارتقاء الى منصب شيخ المهاجرين الجزائريين في توني، هذه الشروط تتمحور حول خدمة أهداف الاحتلال الفرنسي في الجزائر وتونس. كما حرصت الإقامة العامة الفرنسية في تونس على جعله تنظيما رقابيا على المهاجرين الجزائريين المتواجدين بالتراب التونسيين، وفي نفس الوقت كان يروج للسياسة الفرنسية، ويخدم مشروعها من احتلال تونس والجزائر ، كما استخدمته أداة لجمع الضرائب، وتجنيد المهاجرين الجزائريين في الجيش الفرنسي. Résumé : During the French occupation of Algeria in 1830, Tunisia witnessed an increase in the number of Algerian immigrants seeking refuge from French oppressive practices towards the Algerian people, in order to preserve their national identity. As Tunisia became the primary destination for Algerian immigrants, who settled in various regions with political, economic, social, and cultural presence, the Tunisian government and subsequently the French protectorate authorities established an administrative organization to manage the affairs of Algerian immigrants in Tunisia. This was done through the activation of the "Mashyakha" system, serving as a link between Algerian immigrants in Tunisia, the French residency authority, and the Tunisian government, in line with the overall French protection policy in Tunisia between 1881-1956. The Algerian "Mashyakha" organization in Tunisia underwent several developments during the French protectorate period from 1881-1956, evolving from a system managing the Algerian immigrant community in Tunis to representing them to the Tunisian government, to an organization encompassing all Algerian immigrants in Tunisian territories. Conditions were set for aspiring to the position of the Algerian immigrants' leader in Tunis, revolving around serving the goals of the French occupation in Algeria and Tunisia. Furthermore, the French general residency in Tunisia aimed at make it a supervisory organization over Algerian immigrants in Tunisian territories, while simultaneously promoting French policies and serving its agenda of occupying Tunisia and Algeria. It was also utilized as a tool for tax collection and enlisting Algerian immigrants into the French army .
أطروحة دكتوراه
Keywords: المشيخة; الشيوخ الجزائريون; الهجرة; الحماية الفرنسية; تونس; الضرائب; المهاجرون الجزائريون; The Sheikh; Algerian Sheikhs; Emigration; French Protection; Tunisia; Taxes; Algerian Migrants.